Antimicrobial effect of chlorine dioxide on Actinobacillus actinomycetemcomitans in diabetes mellitus rats treated with insulin - Tantin Ermawati; Kwartarini Murdiastuti (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Periodontitis is a chronic inflammatory disease of periodontal tissues. Etiology of periodontal disease includes Actinobacillus actinomycetemcomitans (A. actinomycetemcomitans) which is the most predominant disease-causing bacteria found in the gingival sulcus. Periodontitis can be exacerbated by the systemic disease, such as diabetes mellitus considered as a metabolic disease characterized by hyperglycemia due to insulin deficiency. Treatment of periodontitis is then required in patients with type I diabetes to avoid radical reaction that can not only cause bleeding, but can also prevent infection, as a result, topical antimicrobial therapy and blood glucose control are required. Topical antimicrobial chlorine dioxide is a disinfectant that is effective in killing A. actinomycetemcomitans. Purpose: This study is aimed to determine the effects of topical antimicrobial chlorine dioxide gel or rinse on the number of A. actinomycetemcomitans in DM rats treated with insulin. Methods: 20 three month old male Wistar rats with weight of 170–200 grams were divided into four groups. First, periodontitis and DM were manipulated into all groups through aloksan injection with dose of 170 mg/kg. Those rats in group I were treated with insulin and chlorine dioxide gel, those in group II were treated with insulin and chlorine dioxide rinse, those in group III were treated with insulin only, and those in group IV were without treatment. In the third and seventh weeks, the number of A. actinomycetemcomitans was measured. The data was tested by using One-Way ANOVA test followed by LSD test. Results: The study showed that chlorine dioxide gel has a greater ability in reducing the number of A. actinomycetemcomitans than chlorine dioxide rinse although both are antimicrobials. Conclusion: It can be concluded that the use of chlorine dioxide gel can more effective to decrease the number of A. actinomycetemcomitans than chlorine dioxide rinse in DM rats treated with insulin therapy.Latar belakang: Periodontitis adalah suatu penyakit inflamasi kronis jaringan periodontal. Etiologi penyakit periodontal diantaranya adalah A. actinomycetemcomitans yang merupakan bakteri paling dominan penyebab penyakit yang terdapat pada actinomycetemcomitans yang merupakan bakteri paling dominan penyebab penyakit yang terdapat pada sulkus gingiva. Periodontitis yang terjadi diperparah adanya penyakit sistemik yaitu diabetes mellitus (DM) yang merupakan penyakit metabolik yang ditandai dengan hiperglikemi akibat defisiensi insulin. Perawatan periodontitis pada penderita DM tipe I adalah untuk Perawatan periodontitis pada penderita DM tipe I adalah untuk menghindari tindakan radikal yang dapat menyebabkan perdarahan dan mencegah terjadinya infeksi, sehingga digunakan terapi antimikroba topikal serta kontrol glukosa darah. Antimikroba topikal chlorine dioxide merupakan desinfektan yang efektif dalam membunuh A. actinomycetemcomitans. Tujuan: Penelitian ini bertujuan untuk mengetahui efek antimikroba topikal chlorine dioxide gel atau rinse terhadap jumlah A. actinomycetemcomitans pada tikus DM dengan insulin. Metode: Dua puluh ekor tikus Wistar, jantan, usia 3 bulan, berat 170–200 gram, dibagi menjadi empat kelompok. Semua kelompok sebelumnya dimanipulasi periodontitis serta DM dengan injeksi aloksan dosis 170 mg/kgBB. Kelompok I adalah tikus yang diterapi insulin dan chlorine dioxide gel, kelompok II diterapi insulin dan chlorine dioxide rinse, kelompok III diterapi insulin, serta kelompok IV adalah tikus tanpa dilakukan terapi apapun. Pada minggu ke-3 dan ke-7 dilakukan penghitungan jumlah A. actinomycetemcomitans. Hasil pengukuran di analisis menggunakan uji Anava 1 jalur dilanjutkan dengan uji LSD. Hasil: Penelitian menunjukkan bahwa chlorine dioxide gel mempunyai kemampuan lebih besar dalam menurunkan jumlah A. actinomycetemcomitans dibandingkan chlorine dioxide rinse, walaupun keduanya bersifat antimikroba. Kesimpulan: Dapat disimpulkan bahwa pemberian chlorine dioxide gel lebih efektif menurunkan jumlah A. actinomycetemcomitans dibandingkan kelompok yang diberi chlorine dioxide rinse pada tikus DM dengan terapi insulin.